Role of planar buckling on the electronic, thermal, and optical properties of Germagraphene nanosheets. (January 2023) - Abdullah, Nzar Rauf; Azeez, Yousif Hussein; Abdullah, Botan Jawdat; Rashid, Hunar Omar; Manolescu, Andrei; Gudmundsson, Vidar
Abstract: We report the electronic, the thermal, and the optical properties of a Germagraphene (GeC) monolayer taking into account buckling effects. The relatively wide direct band gap of a flat GeC nanosheet can be changed by tuning the planar buckling. A GeC monolayer has an sp 2 hybridization in which the contribution of an s -orbital is half of the contribution of a p -orbital leading to stronger σ - σ bonds compared to the σ - π bonds. Increasing the planar buckling, the contribution of an s -orbital is decreased while the contribution of a p -orbital is increased resulting in a sp 3 -hybridization in which the σ - π bond becomes stronger than the σ - σ bond. As a result, the band gap of a buckled GeC is reduced and thus the thermal and the optical properties are significantly modified. We find that the heat capacity of the buckled GeC is decreased at low values of planar buckling, which is caused by the anticrossing of the optical and the acoustic phonon modes affecting phonon scattering processes. The resulting optical properties, such as the dielectric function, the refractive index, the electron energy loss spectra, the absorption, and the optical conductivity show that a buckled GeC nanosheet has increased optical activities in the visible light region compared to a flat GeC. The optical conductivity is red shifted from the near ultraviolet to the visible light region, when the planar buckling is increased. We can thus confirm that the buckling can be seen as another parameter to improve GeC monolayers for optoelectronic devices.